Sistem Pendukung Keputusan Pemilihan Karyawan Terbaik Menggunakan Metode Analytic Hierarchy Process (AHP) Pada BMT Al Mubarok Bondowoso - Athorik Ikromi Ramadhanis; Firman Santoso; Lukman Faqih Lidimilah (Universitas Islam Raden Rahmat, Malang, 2024)
Determining top employees is a vital element in human resource management at BMT Al Mubarok Bondowoso. The right decision can improve organizational performance. The research aims to establish a tool to assist in making policies to determine the most outstanding staff through the Analytic Hierarchy Process (AHP) method. AHP was chosen because it can break down complex problems into an easy-to-understand hierarchical structure. The way it works is by recognizing the related parameters in choosing the most outstanding staf, such as performance, discipline, cooperation, initiative, and responsibility. Each criterion is given a weight based on its level of importance through a pairwise comparison process. Furthermore, employees are evaluated based on these criteria to determine the best employee. The research results show that the AHP method is effective in providing objective and systematic recommendations. The developed system produces employee rankings based on the final score from the criteria weights and employee assessments.